Blood Pressure and All‐Cause Mortality by Level of Cognitive Function in the Elderly: Results From a Population‐Based Study in Rural Greece. Issue 2 (19th July 2016) - Georgakis, Marios K.; Protogerou, Athanasios D.; Kalogirou, Eleni I.; Kontogeorgi, Evangelia; Pagonari, Ioanna; Sarigianni, Fani; Papageorgiou, Sokratis G.; Kapaki, Elisabeth; Papageorgiou, Charalampos; Tousoulis, Dimitrios; Petridou, Eleni Th.
Abstract : This study aimed to investigate whether the effect of blood pressure (BP) on mortality differs by levels of cognitive function. The associations of brachial systolic BP, diastolic BP, mean arterial pressure (MAP), and pulse pressure with all‐cause mortality were prospectively explored (follow‐up 7.0±2.2 years) in 660 community‐dwelling individuals (≥ 60 years) using adjusted Cox models, stratified by cognitive impairment (Mini‐Mental State Examination [MMSE] <24). No association between brachial BP variables and mortality was shown for the total sample in quartiles analysis; however, MAP in the highest quartile, compared with the second, was associated with mortality (hazard ratio, 1.85; 95% confidence intervals, 1.09–3.12) among cognitively impaired individuals. The fractional‐polynomials approach for BP confirmed this finding and further showed, solely in the MMSE <24 subcohort, U‐shaped trends of MAP and systolic BP, with increased mortality risk in extremely low or high values; no such pattern was evident for patients with MMSE ≥24. Elderly individuals with cognitive impairment might be more susceptible to the detrimental effects of low and elevated MAP and systolic BP.